The Lemuru Fish Oil and the Suplemen of Vitamin E in the Diet of Broiler Chicken as an Immunomodulator - Rusmana, D; Piliang, WG; Setiyono, A; Budijanto, S (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2008)
The research was conducted using lemuru fish oil and vitamin E supplementation in broiler chicken diet as an immunomodulator. The experiment design was used a completely randomized design with 3 x 3 factorial patern. Nine treatment diets were consisted of three levels of lemuru fish oil supplementation (0, 3, and 6%) as the first factor, and vitamin E supplementation (0, 100, and 200ppm) as the second factor and its combinations. All data were analyzed by analysis of variance and Duncan multiple ranges. There were no significant differences among treatments on antibody titers responses after first ND vaccination, but gave significantly differences on antibody titers (P<0,05) after the second ND vaccination. There were interaction effects of dietary lemuru fish oil and vitamin E on the increasing of the antibody titers. There were no interaction effects of lemuru fish oil and vitamin E on antibody titers responses to IBD. Vitamin E supplementation significantly increased (P<0,05) antibody titers responses to IBD, but not the lemuru fish oil supplementation. The amount of lymphocyte was significantly increased (P<0,05) due to the lemuru fish oil supplementation but not due to the vitamin E supplementation. (Animal Production 10(2): 110-116 (2008) Key Words: Lemuru fish oil, vitamin E, broiler chicken, immunomodulator